Giselle Les sylphides ; Coppélia : ballets - Chopin, Frédéric 1810-1849; Delibes, Léo 1836-1891; Adam, Adolphe 1803-1856; Coralli, Jean 1779-1854 (BBC, under licence to International Classical Artists Ltd, 2012)
The three works represented on this release, along with Tchaikovsky's three balletic masterpieces, comprise a good share of ballet's core repertoire. Giselle, Les Sylphides and Coppélia, having succeeded in their premiere performances, have retained their popularity to the present day ... Les Sylphides is regarded as the first plotless ballet of the twentieth century. As such, it undoubtedly had a significant influence upon the works of George Balanchine who, in his vast output, typically eschewed narrative in favour of composition. Composition is certainly at the heart of Les Sylphides, which begins and ends in a geometrically positioned tableau. Though there is no story here, there is a character who has been variously described as a poet, a dreamer, or, simply, a young man. Dramatically he is a cipher, the only male on the stage, surrounded by diaphanous creatures which sometimes engage him and at other times simply flit around him.
Ballets
Keywords: Ballets; Internet videos